It's About Time: Readiness, Commitment, and Stability in Close Relationships. Issue 8 (November 2019) - Agnew, Christopher R.; Hadden, Benjamin W.; Tan, Kenneth
Timing matters in relationships. People vary in their sense of when they think the time is right to be involved in a committed relationship. We propose and examine the construct of commitment readiness and its role in predicting important relationship outcomes including commitment level, maintenance processes, and stability among involved intimates. Data from five independent samples obtained with various methods revealed, as hypothesized, that readiness (a) predicts commitment, maintenance processes, and actions toward ending a relationship; (b) serves to moderate commitment in predicting maintenance processes (self-disclosure, accommodation, sacrifice); and (c) serves to moderate commitment in predicting leave behavior, with those reporting both higher commitment and higher readiness being more likely to enact maintenance behaviors and least likely to enact leave behavior. We discuss the importance of considering one's readiness for commitment within ongoing involvements.